Replication stress increases mitochondrial metabolism and mitophagy in FANCD2 deficient fetal liver hematopoietic stem cells - Mochizuki-Kashio, Makiko; Otsuki, Noriko; Fujiki, Kota; Abdelhamd, Sherif; Kurre, Peter; Grompe, Markus; Iwama, Atsushi; Saito, Kayoko; Nakamura-Ishizu, Ayako (Frontiers in Oncology, 2023)
Fanconi Anemia (FA) is an inherited bone marrow (BM) failure disorder commonly diagnosed during school age. However, in murine models, disrupted function of FA genes leads to a much earlier decline in fetal liver hematopoietic stem cell (FL HSC) number that is associated with increased replication stress (RS). Recent reports have shown mitochondrial metabolism and clearance are essential for long-term BM HSC function. Intriguingly, impaired mitophagy has been reported in FA deficient cells. We hypothesized that RS in FL HSC impact mitochondrial metabolism to investigate the fetal FA pathophysiology. Results show that experimentally induced RS in adult murine BM HSCs evoked a significant increase in mitochondrial metabolism and mitophagy. Reflecting the physiological RS during development in FA, increase mitochondria metabolism and mitophagy were observed in FA-deficient FL HSCs, whereas BM HSCs from adult FA deficient mice exhibited a significant decrease in mitophagy. These data suggest that RS activates mitochondrial metabolism and mitophagy in HSC.